2021
DOI: 10.35848/1347-4065/abf59a
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the influence of liver microstructure on the evaluation of shear wave velocity

Abstract: Previous studies have shown that evaluation results of shear wave elastography were unstable due to factors such as liver structure and complexity of physical properties. The present study attempts to verify the influence of liver microstructure (fat droplets and fibrous tissue) on the shear wave and shear wave velocity (SWV) evaluation using a shear wave propagation simulation by the elastic finite-difference time-domain method. It was found that disruption of the shear wave causes variations in the SWV of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Ito et al performed a two-dimensional shear wave propagation simulation based on a model simulating the microstructure of fibrous tissue and fat droplets. Their results suggested that wavefront discontinuity of shear waves may be related to the presence of minute fat droplets and affect the SWS [ 84 ].…”
Section: Factors Potentially Affecting Swe Measurementsmentioning
confidence: 99%
“…Ito et al performed a two-dimensional shear wave propagation simulation based on a model simulating the microstructure of fibrous tissue and fat droplets. Their results suggested that wavefront discontinuity of shear waves may be related to the presence of minute fat droplets and affect the SWS [ 84 ].…”
Section: Factors Potentially Affecting Swe Measurementsmentioning
confidence: 99%
“…2(b), the position and time of the peak of the shear wave were tracked along the direction perpendicular to the propagation direction of the push pulse. Finally, the SWS was measured using the time of flight (TOF) method, 31,32) which calculates the proportionality coefficient between the travel time and travel distance, as shown in Fig. 2(c).…”
Section: Sws Measurementmentioning
confidence: 99%
“…We have developed a method for analyzing moving sound sources and receivers using the finite difference-time domain (FDTD) method. [6][7][8][9][10][11][12][13][14][15][16] We have previously implemented moving sound sources and receivers with omni-directional directivity in the two-dimensional (2D) 17,18) and threedimensional FDTD methods. 19) Furthermore, we have implemented movings sound sources and receiver with simple directivity, such as dipole and cardioid, in two-dimensions 20) and three-dimensions.…”
Section: Introductionmentioning
confidence: 99%